Dissociation and re-imagination: the publicity of Chinese marriage law and divorce narrative in the 1950s - Luo, Yingyu (2024)
After the promulgation of the Marriage Law of the People’s Republic of China in 1950, literary works engendered from the exigencies of publicity held distinct policy implications and disciplinary significance. Given that the issue of divorce encapsulates both the rationale of “free rights” and the sensibility of social disorder, the narrative of “divorce” during this period is, to some extent, situated between politics and reality. On the one hand, literary works must positively advocate the legal concept of “divorce freedom”, while, on the other hand, they must also undergo a delicately nuanced narrative processing to circumvent sensitivities. Consequently, the depiction of divorce narratives is characterized by ambiguity and capriciousness. Nonetheless, literature has to some extent bridged the gap between law and reality by reimagining the genuine predicaments triggered by divorce.